Employees Performance Measurement and Increasing in Digital Era: A Study From the Perspective of Developing Economies - Darpan Tripathi; Ibrar Khan (Business Review of Digital Revolution, 2023)
With a focus on private telecommuting businesses in Pakistan, this study investigates the effects of online training, online monitoring, and external motivation on worker performance in the setting of emerging economies. The goal of this study was to investigate the relationship between these independent variables and the dependent variable of employee performance. A quantitative research methodology was used to achieve this goal. Managers of private Pakistani telecommuting companies were asked to complete a survey to gather data. The questionnaire covered topics such as online training, online monitoring, outside motivation, and employee performance. The findings of the study showed that online training significantly improved worker performance. Additionally, it was discovered that online monitoring was favorably related to worker performance. Additionally, it was discovered that external incentives significantly affected employee performance. These results lead to the conclusion that external incentive, online monitoring, and online training are key elements in improving employee performance in the digital age. To increase employee performance, businesses in developing countries like Pakistani private telecommuting corporations can think about applying these tactics. For managers and decision-makers constructing efficient performance measurement systems to boost productivity and success in the emerging nations’ expanding digital landscape, this study offers helpful insights.
Keywords: Online Training; Online Monitoring; External Motivation; Employee Performance